PERANAN SENI TILAWAH DALAM MEMPERBAIKI DAN MEMPERINDAH BACAAN AL-QUR’AN DI PONDOK PESANTREN AL-FALAH PUTRI BANJARBARU - Elsi Saputri; Muhammad Helmi (Program Studi PAI STAI Al Falah Banjarbaru, 2025)
Reading the Qur'an with a beautiful voice and a variety of songs makes the listeners amazed when read in accordance with the makhraj and the laws of tajweed. Pesantren Al-Falah Putri Banjarbaru, one of which has an extracurricular tilawah which has only been running since 2024. The reason for the extracurricular program is so that it can be a positive value for the boarding school to be able to produce quality qoriah. The purpose of this research is to find out how the role of tilawah art in improving and beautifying the reading of the Qur'an at the Al-Falah Putri Banjarbaru Islamic boarding school and to find out the supporting and inhibiting factors. This type of research is descriptive field research and the approach used is a qualitative approach. The subject of this research is ustadzah who teaches tilawah art. While the object of this research is the Role of Tilawah Art in Improving and Beautifying the Recitation of the Qur'an at Pondok Pesantren Al-Falah Putri Banjarbaru. Data extraction using observation, interview and documentation techniques. While data processing techniques are carried out by editing, data classification and data interpretation and then making conclusions by means of inductive. Based on the results of the study, it can be concluded that the role of tilawah art in improving and beautifying the recitation of the Qur'an in Pondok Pesantren Al-Falah Putri Banjarbaru has been well implemented. The role of tilawah art that has been carried out includes improving the quality of reading the Qur'an, beautifying the reading of the Qur'an, increasing understanding of the Qur'an and the formation of motivation in reading the Qur'an. Supporting factors include the existence of a mentor teacher, infrastructure and motivation, while inhibiting factors include little time and lack of parental attention.